Hydrothermal dolomitization in a complex geodynamic setting (Lower Palaeozoic, northern Spain) - Lapponi, Fabio; Bechstädt, Thilo; Boni, Maria; Banks, David A.; Schneider, Jens (Sedimentology, 2014)
Burial hydrothermal dolomitization is a common diagenetic modification in sedimentary basins with implications for oil and gas reservoir performance. Outcrop analogues represent an easily accessible source of data to refine the genetic models and assess risk in hydrocarbon exploration and production. The Palaeozoic succession of northern Spain contains numerous excellent exposures of epigenetically dolomitized limestones, particularly in the Carboniferous and Cambrian. The epigenetic dolomites in the Cambrian carbonates of the Láncara Formation are volumetrically small, but have a large aerial distribution across different tectonic units of the Variscan fold and thrust belt. Coarse crystals, abundant saddle dolomite cement, negative δ18O and fluid inclusion homogenization temperatures between 80°C and 120°C characterize these dolomites, which are petrographically and geochemically similar to the tens of kilometre-sized hydrothermal dolomites replacing the Upper Carboniferous succession in the same area. In both cases, the dolomitizing fluids are derived from highly evaporated sea water, modified to a limited degree through fluid-rock interaction. The dolomitization events affecting both Cambrian and Carboniferous strata are probably related to the same post-orogenic hydrothermal fluid flow. The formation of the post-collisional (latest Carboniferous) Cantabrian arc fostered dolomitization: the extension related to bending of the arc generated deep-reaching faults and strike-slip movements, which favoured the circulation of hot dolomitizing fluids in the outer parts of this orocline. A similar dolomitization process affected other areas of Europe after the main stages of the Variscan orogeny. Dolomitization was a continuous, uninterrupted, isochemical process. Limestone replacement resulted in a major porosity redistribution and focused the fluid flow into the newly created porous zones. Replacement was followed immediately by partial to complete cementation of the pores (including zebra fabrics and vugs) with saddle dolomite. The amount of porosity left depends on the volume of cement and therefore on the volume of fluids available.